Pollution of “Akmenės cementas” vicinity: alkalizing microelements in soil, composition of vegetation species and projection coverage - Stravinskienė, Vida (Journal of Environmental Engineering and Landscape Management, 2011)
The article presents the results of the research pertaining to forest litter and the composition of peat topsoil microelements, as well as the composition and projection coverage of undergrowth, herbaceous and bryophyte species specific to the vicinity of the cement factory “Akmenes cementas” are presented. Increased amounts of strontium, barium, titanium, manganese, copper, chromium, nickel and boron in forest litter and the upper 10 cm peat layer (up to 6 km from the pollution source) were established. 53 plant species were observed. The greater part (75–81%) of them are vascular plants. It was indicated that the diversity of vegetation species at different distances (0.5–1.0, 3.0–3.5 and 5.5–6.0 km) from the pollution source varies. Species of broadleaved trees and shrubs (Quercus robur L., Betula pendula Roth., Frangula alnus Mill., Corylus avellana L.), resistant to the impact of alkaline dust, are more outspread near the pollution source. Nearby the pollution source (0.5–1.0 km), Campylium stellatum Lange and Campylium sommerfeltii Lange, were found. At the farthest distances from the plant, the typical for Myrtillo-oxalidosa site type moss Hylocomium splendens (Hedw.) Schimp., Rhytidiadelphus triquetrus (Hedw.) Warnst, and herbs Epilobium palustre L., Vaccinium myrtillus L., Moehringia trinervia (L.) Clairv. were observed. Total coverage of vegetation species varied from 35.5±1.9% at the closest to the pollution source distance to 19.6±2.1% at the 3.0–3.5 km distance. It is significantly (p;